Resilience Enhancement for Distribution Networks Under Typhoon-Induced Multi-Source Uncertainties - Naixuan Zhu; Guilian Wu; Hao Chen; Nuoling Sun (Energies)
The increasing prevalence of extreme weather events poses significant challenges to the stability of distribution networks (DNs). To enhance the resilience of DNs against such events, a typhoon-oriented resilience framework for DNs is proposed that incorporates multiple sources of typhoon uncertainty. First, component failure probability is modeled by tracking time-sequential variations in typhoon landfall parameters, trajectory, and intensity, thereby improving the quantitative estimation of typhoon impacts. Then, the integrated component failure probability and the importance factor of bus load under disaster are combined and hierarchical analysis is performed to achieve the vulnerability identification for DNs. Next, based on the vulnerability identification results, a resilience enhancement model for DNs is constructed through the strategy of coordinating line reinforcement and energy storage configuration, and the resilience optimization scheme that takes into account the system resilience enhancement effect and economy is obtained under the optimal investment cost. Finally, analysis and verification are conducted in the IEEE 33-bus system. The results indicate that the proposed method can reduce the load loss cost of the system by 5.112 million and 0.2459 million, respectively.